Риск развития послеоперационного гипопаратиреоза в зависимости от обьема операции на щитовидной железе - Завгородний, С. Н.; Рылов, А. И.; Данилюк, М. Б.; Доля, О. С.; Ярешко, Н. А.; Zavgorodniy, S. M.; Rylov, A. I.; Danylyuk, M. B.; Dolya, O. S.; Yareshko, N. A.; Завгородній, Сергій Миколайович; Рилов, Андрій Іванович; et al. (Белорусский государственный медицинский университет, 2017)
Целью исследования было определить степень риска развития послеоперационного гипопаратиреоза в зависимости от объема оперативного вмешательства на щитовидной железе, при выполнении тиреоидэктомии и различного вида лимфатической диссекциишейных лимфатических колекторов. За период с 2014 по 2016 год выполнено 167 оперативных вмешательства по поводу многоузлового зоба 3—4 ст. и високодифференцированного рака щитовидной железы. Все пациенты были разделены на 3 группы по отношению к объему оперативного вмешательства: группа А — больные, которым выполнена тиреоидэктомия — 45 пациентов (26,9%), группа В — тиреоидэктомия и центральная лимфодиссекция (удаление 6-й группы лимфатических узлов шеи) — 54 больных (32,4%), группа С — больные, которым выполнена тиреоидэктомия, центральная и латеральная лимфодиссекция (удаление 3 и 4 — й группы лимфатических узлов) — 68 (40,7%). The aim of the study was determine the degree of risk of postoperative hypoparathyroidism, depending on the volume of surgery on the thyroid gland, in the performance of various types of thyroidectomy and various kinds of lymphatic dissection of lymph collectors. During the period from 2014 to 2016 performed 167 surgical interventions for multinodular goiter 3—4 st. and thyroid cancer. All patients were divided into 3 groups based on the volume of surgery: group A-patients who underwent thyroidectomy — 45 patients (26.9%), Group B — thyroidectomy and central lymph node dissection (removal of the 6th Group of lymph nodes in the neck) — 54 patients (32.4%), group C — patients who underwent thyroidectomy, central and lateral lymph node dissection (removal of 3 and 4 groups of lymph nodes) — 68 (40.7%). According to the following conclusions obtained results: the volume of surgery is directly proportional effect on the risk of transient hypoparathyroidism in the early postoperative period. At the same time the size of the thyroid gland at this rate is not affected. The main factor determining the development of hypocalcemia after operation is the level of parathyroid hormone on the second day after the operation lower 11.0 pg / mL. The postoperative level of parathormone higher 11.0 pg/ml excludes the subsequent development of symptomatic hypocalcemia. The risk of developing persistent hypoparathyroidism does not depend on the volume of surgery on the thyroid gland.
Risk of development of a postoperative gipoparatireoz depending on the volume of operation on a thyroid gland
Keywords: гипопаратиреоз; паратгормон; рак щитовидной железы; тиреоидэктомия; кальций; hypoparathyroidism; thyroid cancer; parathormone; thyroidectomy; calcium